2020
DOI: 10.1007/s00268-020-05600-4
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bedside Peritoneal Dialysis Catheter Placement in the COVID‐19 Era: Initial Experience at a New York City Hospital

Abstract: Introduction Acute kidney injury (AKI) requiring renal replacement therapy (RRT) is common in critically ill patients with COVID-19. Unparalleled numbers of patients with AKI and shortage of dialysis machines and operative resources prompted consideration of expanded use of urgent-start peritoneal dialysis (PD) and evaluation of the safety and efficacy of bedside surgical placement of PD catheters. Study design Bedside, open PD catheter insertions were performed in early April 2020, at a large academic center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Although others have reported the use of PD during the COVID-19 pandemic, 12 , 13 , 14 our study is the largest to date and the only one to describe bedside percutaneous catheter insertion (as opposed to open or laparoscopic surgical insertion). In our study, no complications leading to significant harm were reported following catheter insertion, even in patients with failed catheter insertion attempts.…”
Section: Discussionmentioning
confidence: 97%
“…Although others have reported the use of PD during the COVID-19 pandemic, 12 , 13 , 14 our study is the largest to date and the only one to describe bedside percutaneous catheter insertion (as opposed to open or laparoscopic surgical insertion). In our study, no complications leading to significant harm were reported following catheter insertion, even in patients with failed catheter insertion attempts.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, the emerging literature highlights that the number of patients with AKI requiring CRRT is unprecedented in modern history [ 53 ]. These therapeutic interventions have proved fundamental as lifesaving measures in patients with severe forms of COVID-19 and impaired renal function [ 153 , 154 , 155 ].…”
Section: Therapeutic Strategies In Sars-cov-2–induced Akimentioning
confidence: 99%
“…Each site identified one key nephrologist with PD experience to coordinate urgent start PD. We identified general or transplant surgeons who could perform bedside PD catheter insertion in accordance with International Society of Peritoneal Dialysis (ISPD) guidelines (11)(12)(13). To ensure effective PD delivery, we excluded patients with extensive surgical history, ascites, active gastrointestinal issues, who required prone ventilation or had high oxygen/PEEP requirements.…”
Section: Peritoneal Dialysismentioning
confidence: 99%